Interaction between an entomopathogenic fungus Metarhizium anisopliae and its host subterranean termites Coptotermes curvignathus during infection process - Samsuddin, Ahmad Syazwan (2017)
The subterranean termites, Coptotermes curvignathus is a destructive pest of tree plantation in Malaysia. Controlling termite population by chemical is not a good option since it may increase the resistance of pest towards the pesticide and cause several implications towards biodiversity and environment. Metarhizium anisopliae, an entomopathogenic fungus is a good option by controlling the termite biologically. In this study, ten M. anisopliae isolates were screened for their pathogenic effect on termites. The best isolate, PR1 which originated from Pantai Remis, Selangor is the most prudently isolates by yielded the highest mortality (96.97%) and the shortest median lethal time (LT50= 1.47 days). This isolate was utilized in downstream study by conducting the histopathology and protein expression study; for each stages of pathogenesis up to 144 h of post-inoculation. Results demonstrated that it requires two days to kill infected host starting by germ tube penetration through the termite cuticle observed at 6 h postinoculation. Injury caused by M. anisopliae’s appressorium in a way to penetrate the first layer of host defense mechanism, the cuticle, one of the factors that weakening the infected host. Dissemination and of fungal and hyphal bodies observed on cellular level is a proof that M. anisopliae invaded the host starting from the cellular level. Then, inoculated termites were mummified and the sporulation of M. anisopliae on host’s carcasses observed at 96 h and 144 h of post-inoculation, respectively. Meanwhile in protein expression study, four and five significance expressed proteins have been identified from C. curvignathus and M. anisopliae, respectively. Expressed proteins in termite shows evidence that being involve in cell regulation and immune response towards infection by this entomopathogenic fungus. Meanwhile, the expressed proteins extracted from M. anisopliae were discovered to be involved in the protein transportation and also related with fungus virulencity during infection process. By knowing the interaction between this host-pathogen relationship, the achieved knowledge could be utilized in future development of biopesticide by using this fungus to control termite population effectively.